NATIONAL SEMINAR ON â€œPRIORITIES IN FISHERIES AND AQUACULTUREâ€ HELD AT COLLEGE OF FISHERIES, OUAT, RANGEILUNDA, ODISHA - Mohanty, BIMAL PRASANNA (Journal of the Inland Fisheries Society of India, 2021)
Inland Fisheries Society of India (IFSI) in collaboration with ICAR-Central Inland Fisheries Research Institute, Barrackpore, West Bengal; College of Fisheries, OUAT, Rangeilunda, Odisha and Fisheries College Alumni Association (OFCAAR) have jointly organized the National Seminar on â€œPriorities in Fisheries and Aquacultureâ€ at College of Fisheries, Rangeilunda, Berhampur, Odisha during 11-12, March 2017. The Seminar was inaugurated on 11th March, 2017 in the auditorium of College of Fisheries, Rangeilunda, Odisha with the lighting of lamp by Chief Guest Shri. Bishnupad Sethi, IAS, Commissioner cum Secretary, Government of Odisha in presence of other honoured guests. The inaugural session was presided over by Dr. J. K. Jena, DDG (Fisheries Science) ICAR, New Delhi. Dr. (Mrs.) Shyama Mishra, Director, College of Fisheries, Rangeilunda welcomed all the dignitaries and the participants. Dr. Basanta Kumar Das, Director, ICAR-CIFRI, Barrackpore and Convenor of the National seminar extended a warm welcome to all participants and gave a brief account of the purpose and objectives of the seminar. Dr. N. P. Srivastava, Secretary, IFSI, Kolkata welcomed all the dignitaries and participants on behalf of the society. Dr. Jitendra Kumar Sundaray, Director (Acting), ICAR-CIFA, Bhubaneswar, Odisha in his address stressed on generating new age entrepreneurship in fisheries and aquaculture in Odisha and other states through convergence of all ICAR institutes in the region. Dr. N. Sarangi, former Director, ICAR-CIFA, Bhubaneswar hoped that this seminar will come up with good recommendations for fisheries and aquaculture development in India. Dr. S. Dam Roy,Â Director, ICAR-CIARI, Port Blair, Andaman and Nicobar Island emphasized on the role played by fisheries in livelihood security. Dr. S. D.Tripathi, Former Director & VC, ICAR-CIFE, Mumbai and Dr. Dilip Kumar, former Director ICARCIFE, Mumbai and FAO Expert expressed their views and hope for grand success of this programme